2021
DOI: 10.1016/j.eclinm.2021.100961
|View full text |Cite
|
Sign up to set email alerts
|

Performance of point-of-care tests for the detection of chlamydia trachomatis infections: A systematic review and meta-analysis

Abstract: Background Chlamydia trachomatis (CT) is one of the most prevalent bacterial sexually transmitted infections (STIs) globally but has been inadequately detected for intervention. Introduction of point-of-care tests (POCTs) for CT is critical for filling the intervention gaps. We conducted a systematical review and meta-analysis on diagnostic performance of POCTs for CT to assist in guiding the application of these assays in CT screening and detection. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 70 publications
(114 reference statements)
1
5
0
Order By: Relevance
“…Our results are in accordance with a meta-analysis conducted by Zhou et al 7 on POCTs (NAATs or antigen-detection tests) for CT screening that excluded POCT performance with SS. Our results complement a meta-analysis comparing SS with clinician sampling for CT/GC conducted by Lunny et al 8 years ago.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are in accordance with a meta-analysis conducted by Zhou et al 7 on POCTs (NAATs or antigen-detection tests) for CT screening that excluded POCT performance with SS. Our results complement a meta-analysis comparing SS with clinician sampling for CT/GC conducted by Lunny et al 8 years ago.…”
Section: Discussionsupporting
confidence: 92%
“…A systematic review reported higher accuracy of nucleic acid amplification tests (NAATs) for CT detection compared with antigen-based tests but failed to evaluate SS 7. A systematic review by Lunny et al , published 8 years ago, reported comparable accuracy of self-obtained samples with clinician-obtained samples (n=6100 paired samples) 8.…”
Section: Introductionmentioning
confidence: 99%
“…The nature of the populations tested, small sample numbers, and the diverse diagnostic techniques further influence results (66). Furthermore, testing techniques vary substantially and approaches, such as nucleic acid amplification tests, which has been proven to be more sensitive and specific, compared to enzyme immunoassay tests, may require transport to specialize laboratory, as well as specialized equipment and staff, delaying the availability of results for rapid management choices in certain regions (67). As a result, in some cases, the most accurate test may not be the approach eventually used.…”
Section: Figurementioning
confidence: 99%
“…The efforts in PICTs to improve testing for and surveillance of HIV and syphilis have unfortunately not been replicated for C. trachomatis and N. gonorrhoeae. This is due to several reasons, including a lack of accurate, affordable tests [72]. Neither C. trachomatis nor N. gonorrhoeae are routinely tested for or reported in most PICTs.…”
Section: Historical and Current Approaches To Sti Testing In Pictsmentioning
confidence: 99%